Тurbulent natural convection modeling in enclosed tall cavities - Goloviznin, Vasiliy Mikhailovich; Korotkin, Ivan Aleksandrovich; Finogenov, Sergey Aleksandrovich (Computational Continuum Mechanics, 2016)
In our previous work on the parameter-free numerical method for modeling thermal convection in square cavities in a wide range of Rayleigh numbers (Computational Continuum Mechanics, 2015, vol. 8, no. 1, pp. 60-70), it was shown that using eddy-resolving parameter-free CABARET scheme for solution of both two and three dimensional Davis’ test leads to surprisingly good agreement of computational results on the coarse grids (20×20) and (20×20×20) with experimental results and accurate computations for Rayleigh numbers up to 10^14. Current work is devoted to sensitivity analysis of this phenomenon in terms of cavity form variation from cubical to highly stretched. Therefore, the computational regions with the aspect ratio 1:4, 1:10, and 1:28.6 were considered. Comparison of CABARET scheme results with the experimental data (for the aspect ratio 1:28,6), DNS results (for the ratio 1:4), and empirical relation (for the ratio 1:10) is presented. In all the cases CABARET method showed good agreement of integral parameters of the flow with the results of other authors. For CABARET calculations notably coarse grids were used with refining to the walls of the region. It is shown that acceptable computation accuracy on the extremely coarse grids is achieved for the aspect ratio up to 1:10. For the higher aspect ratio and the given accuracy the number of computational cells significantly grows